Hieroglyphica (2009)
[Dt.:] Die Seite des Ägyptologen Maxim Panov stellt einen Editor für ägyptische Hieroglyphen mit ca. 4600 Zeichen zum freien Download für das Betriebssystem Windows zur Verfügung. Die Möglichkeiten des Programms sind im einzelnen aufgelistet. Außerdem bietet die Website zahlreiche Texte des Autors an. Für deren Download muss man sich jedoch als Benutzer registrieren lassen. - [Engl.:] This site from the Russian Egyptolgist Maxim Panov offers an editor for egyptian hieroglyphs with about 4600 signs for free downloading (for windows systems). Also texts of the author are listed and can be downloaded. For the download of these registration is required.